Green Accounting Disclosure As A Determinant Of Financial Report Performance And Company Value, Best Manufacturing Companie Based On Forbes Indonesia Magazine - Aruning Puspita, Dyah; Kautsar Ramdhani , Amritsal; Sugiono, Djoko (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
This research aims to determine and explain the effect of green accounting disclosure variables on company financial performance and firm value. This type of research used in this research is quantitative research. The variables in this study are green accounting disclosure as the independent variable, company financial performance and firm value as the dependent variable. This study uses secondary data on the 50 best manufacturing companies based the Indonesian Forbes magazine that participated in the PROPER program. The results show that: there is no significant effect between Green Accounting Disclosure on Company Financial Performance and there is a significant negative effect between Green Accounting Disclosure on Firm Value